Spontaneous Age-Related Histopathological Changes in Microminipigs. (October 2019) - Kangawa, Akihisa; Nishimura, Toshiaki; Nishimura, Takashi; Otake, Masayoshi; Enya, Satoko; Yoshida, Toshinori; Shibata, Masatoshi
Microminipigs have become an attractive animal model for toxicology and pharmacology studies and for human disease models, owing to their manageable size. Although there are numerous reports of spontaneous age-related lesions in mice, rats, dogs, and monkeys, those in minipigs are scarce. In the present study, spontaneous age-related histopathological changes were investigated using 37 microminipigs (20 males and 17 females) that were 6 months to 10 years of age. Abnormal deposits of materials were evident in several animals from 6 years of age, and these deposits included amyloid in the renal medulla, thyroid gland, and adrenal gland, hyaline droplets in glomeruli, and fibrillar inclusions in neurons. Arterial sclerosing changes (intimal thickening, intimal proliferation, and medial mineralization) and proliferative lesions (hyperplasia of hepatocytes, follicular cells, Leydig cells, and uterine endometrial glands) were present at 4 years of age and beyond. Renal adenoma, uterine leiomyoma, and Leydig cell tumor were observed in several microminipigs. Moreover, glomerulosclerosis, renal interstitial fibrosis, thymic involution, and adrenocortical cell vacuolation were common in aging microminipigs. Since knowledge of age-related changes is helpful for pathologists, the basic information obtained in this study will be a useful reference for all future toxicity evaluations in microminipigs.